Dimensi Sosiologi Sekolah Berkeadilan Menurut Perspektif Masyarakat Pendidikan (Studi Kasus di Kota Makasar dan Kabupaten Bulukumba) - - Basrowi (Universitas Negeri Yogyakarta, 2007)
This study aims at describing principles of fairness education examined from intellectual and financial aspects of sociology in the social perspectives. Relying on the quantitative approach, this study collected data using survey, observation, in depth interview, and documentary analysis. Area sampling techniques were used in this study involving one countries and one cities in the Makasar provinces. The number of respondents and their areas were 2 persons from Education Department Office, 12 principals, 12 school-teachers, 12 student-parents, 3 members of School Committee, and 24 students. Data of this study were analyzed using tabulation techniques focusing on the frequency and rate percentage. Three findings were revealed in this study. First, schools that have conducted principles of fairness education included schools that opened acceleration classes, superior classes, SNBI classes, bilingual classes, and inclusive or integrated classes. Second, schools that implemented principles of fairness education emphasizing on financial aspects were schools that gave scholarships and cross-subsidy. Third, schools that accommodated principles of fairness education based on the intellectual aspect put strong emphasis on the quality of input students. In addition, financial aspects in the implementation of principles of fairness education included economy status of students parents, school budget condition, support from local government, support from school committee, and support from stakeholders.